The Effect of Financial-Related Experience, Behavioral Intention, Spiritual Intelligence and Gender on Family Financial Behavior - Purwidianti, Wida; Darmawan, Akhmad; Melliana, Sinta Bella (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2019)
This study aims to determine the effect of financial-related experience, behavioral intention, spiritual intelligence and gender on family financial behavior. The population of this research was families in Sumbang Sub-district, Banyumas Regency, Central Java. A total of 174 were involved. Multiple regression analysis was used to examine the effect of financial-related experience, behavioral intentions, spiritual intelligence, and gender on family financial behavior. The results revealed that financial-related experience, behavioral intention, and gender partially had a significant positive effect on family financial behavior. Meanwhile, spiritual intelligence had no significant effect on financial behavior. The findings of this study are expected to encourage policy-maker for paying attention to factors that affect family financial behavior.